THE IMPACT OF COVID-19 ON TAX ADMINISTRATION IN THE REPUBLIC OF CROATIA (EU and comparative law issues and challenges series (ECLIC), 2021)
The crisis and special measures caused by the Covid-19 virus pandemic have greatly disrupted the business and survival of small and medium-sized enterprises, as well as larger industries. The state and its institutions were forced to take certain measures to facilitate the survival and continuation of business, and to save jobs for entrepreneurs and their employees.  The Tax Administration is a state institution whose measures directly affect every business. So it was among the first to take some measures, i.e. to adjust its business and tax collection to the new situation. This paper discusses the first measures introduced, those from March and April 2020. It discusses the deferral or installment payment of due and deferred tax liabilities. The measure of deferral, installment payment of tax liability, is certainly the most important and most popular measure among taxpayers. It is explained how tax measures during a pandemic should look according to the recommendations of the Organization for Economic Co-operation and Development (OECD). We explain other measures that have been introduced to facilitate business. These are the extension of the deadline for filing income tax, the exemption from VAT, the enforcement procedure and the payment of the annual tax rate. Despite the measures taken so far, it is important to emphasize that the Covid-19 pandemic is still ongoing, and that according to some experts, a real crisis with visible consequences of the pandemic is still to be expected. Accordingly, it is to be expected that the current measures are very likely to be further changed, upgraded and adjusted as the situation changes. We consider it important to note that the framework of this paper does not allow a detailed analysis and that we are forced to limit ourselves exclusively to some aspects of the issue at hand.